Foraminiferal assemblages in the mangrove sediments of Kemaman and Tumpat, east coast of peninsular Malaysia - Rokiah Suriadi (Terengganu: Universiti Malaysia Terengganu, 2012)
Widely known for their importance in the oil exploration activities, the study of foraminifera is always the basis of finding a new oil rig or dating of rock fossils. Little is known about their ecological distribution, biological systems, as well as their response towards a variety of environments.